The political economy of financial regulation - Rainer Haselmann; Arkodipta Sarkar; Shikhar Singla; Vikrant Vig (Goethe University, Center for Advanced Studies on the Foundations of Law and Finance (LawFin), 2022)
Increased interdependencies across countries have led to calls for greater harmonization of regulations to prevent local shock from spilling over to other countries. Using the rulemaking process of the Basel Committee on Banking Supervision (BCBS), this paper studies the process through which harmonization is achieved. Through leaked voting records, we document that the probability of a regulator opposing an initiative increases if their domestic national champion (NC) opposes the new rule, particularly when the proposed rule disproportionately affects them. Next, we show that smaller banks, even when they collectively have a higher share in the domestic market, do not have any impact on regulators' stand - suggesting that regulators' support for NCs is not guided by their national interest. Further, we find the effect is driven by regulators who had prior experience working in large banks. Finally, we show this unanimous decision-making process results in significant watering down of proposed rules. Overall, the results highlight the limits of harmonization of international financial regulation.
Keywords: P43; G28; G21; 330; Political Economy; Financial Regulation; Textual Analysis